Rapid supersonic spraying of Cu(In, Ga)(S, Se)2 nanoparticles to fabricate a solar cell with 5.49% conversion efficiency. (15th January 2017) - Park, Jung-Jae; Lee, Jong-Gun; Kim, Do-Yeon; Lee, Jong-Hyuk; Yun, Jae Ho; Gwak, Jihye; Eo, Young-Joo; Cho, Ara; Swihart, Mark T.; Al-Deyab, Salem S.; Ahn, SeJin; Kim, DongHwan; et al.
Abstract: We demonstrate production of high-quality Cu(InGa)(SSe)2 (CIGSSe) films by high-rate supersonic spray deposition. This technique is unique in creating particle-based films without introducing impurities, because no additives or binders are used. The thin film deposition process was investigated computationally, to understand the pulverization of the incoming particles. These simulations were consistent with experimental observations. Grain growth was improved by adding a 300-nm copper layer atop the CIGSSe film; selenization of the resulting bilayer produced a CuSe liquid flux that assisted the sintering process. The final CIGSSe film-based solar cell had a conversion efficiency of 5.49% with J sc  = 18.73 mA/cm 2, V oc  = 0.488 V, and FF  = 59.99% in an active area of 0.44 cm 2 . Graphical abstract: We demonstrated that the supersonic spray technique is extremely versatile and scalable for fabricating thin film solar cells. Computational simulations are also included to elucidate the deposition mechanism of the nanoparticles impacting at supersonic speed; the comparison between the experiment and simulation were consistent and they were in good phenomenological agreement. To this end, the proposed supersonic spraying could help to fulfill the translational potential of CIGS films by bringing them from the laboratory into real-world applications. Image 1